Unenhanced third-generation dual-source chest CT using a tin filter for spectral shaping at 100kVp - Haubenreisser, Holger; Meyer, Mathias; Janssen, Sonja; Schönberg, Stefan; Henzler, Thomas (European journal of radiology, 2015)
Objective: To prospectively investigate image quality and radiation dose of 100kVp spectral shaping chest CT using a dedicated tin filter on a 3rd generation dual-source CT (DSCT) in comparison to standard 100kVp chest CT. Methods: Sixty patients referred for a non-contrast chest on a 3rd generation DSCT were prospectively included and examined at 100kVp with a dedicated tin filter. These patients were retrospectively matched with patients that were examined on a 2nd generation DSCT at 100kVp without tin filter. Objective and subjective image quality was assessed in various anatomic regions and radiation dose was compared. Results: Radiation dose was decreased by 90% using the tin filter (3.0 vs 0.32mSv). Soft tissue attenuation and image noise was not statistically different for both examination techniques (p>0.05), however image noise was found to be significantly higher in the trachea when using the additional tin filter (p=0.002). SNR was found to be statistically similar in pulmonary tissue, significantly lower when measured in air and significantly higher in the aorta for the scans on the 3rd generation DSCT. Subjective image quality with regard to overall quality and image noise and sharpness was not statistically significantly different (p>0.05). Conclusion: 100kVp spectral shaping chest CT by means of a tube-based tin-filter on a 3rd generation DSCT allows 90% dose reduction when compared to 100kVp chest CT on a 2nd generation DSCT without spectral shaping.